The Effect Of Surah Waqiah Murotal Therapy On Anxiety Reduction In The Exit Exam Competency Test - Dadi Hamdani; Andan Firmansyah; Ade Fitriani; Suhanda Suhanda; Henri Setiawan (LP3M Universitas Muhammadiyah Tasikmalaya, 2023)
Competency tests often make students vulnerable to experiencing stress, especially during the current Covid-19 pandemic. The coping mechanism used by students greatly determines the success of students in facing competency tests. Data for passing the national nurse competency test in the last 2 years 2020-2021 averaged only 79.67% passing which is still far from expectations. Murottal Al-Qur'an has a relaxing effect, reduces stress and anxiety. The purpose of this research is to prove the effect of waqiah letter murottal therapy in managing emotions when facing the nurse's exit exam competency test. Research design used a quasy-experiment pre and post-test design with 2 intervention and control groups with a sample of 60 people. Respondents' stress levels were measured quantitatively using research instruments before and after the recitation intervention using the DASS scale. Based on data analysis, it is known that the p-value is 0.001 or p-value <0.05, which means that there is an effect of waqiah recitation therapy on reducing stress in students who will carry out the nurse competency test.